Usher Syndrome: Genetics and Molecular Links of Hearing Loss and Directions for Therapy - Whatley, Meg; Francis, Abbie; Ng, Zi Ying; Khoh, Xin Ee; Atlas, Marcus D.; Dilley, Rodney J.; Wong, Elaine Y. M. (Frontiers in Genetics, 2020)
Usher syndrome (USH) is an autosomal recessive disorder that permanently and severely affects the senses of hearing, vision and balance. Three clinically distinct types of USH have been identified, decreasing in severity from Type 1 to 3, with symptoms of sensorineural hearing loss, retinitis pigmentosa and vestibular dysfunction. There are currently nine confirmed and two suspected USH-causative genes, and a further three candidate loci have been mapped. The proteins encoded by these genes form complexes that play critical roles in the development and maintenance of cellular structures within the inner ear and retina, which have minimal capacity for repair or regeneration. In the cochlea, stereocilia are located on the apical surface of inner ear hair cells and are responsible for transducing mechanical stimuli from sound pressure waves into chemical signals. These signals are then detected by the auditory nerve fibres, transmitted to the brain and interpreted as sound. Disease-causing mutations in USH genes can destabilise the tip links that bind the stereocilia to each other, and cause defects in protein trafficking and stereocilia bundle morphology, thereby inhibiting mechanosensory transduction. This review summarizes the current knowledge on Usher syndrome with a particular emphasis on mutations in USH genes, USH protein structures, and functional analyses in animal models. Currently, there is no cure for USH. However, the genetic therapies that are rapidly developing will benefit from this compilation of detailed genetic information to identify the most effective strategies for restoring functional USH proteins.